Perancangan User Experience Aplikasi Manajemen Keuangan Rukun Tetangga menggunakan Metode Human-Centered Design. Studi Kasus: Perumahan River Village Blok E2 Kota Malang - Zalfa Rossana; Riswan Septriayadi Sianturi; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Neighborhood pillars are institutions formed by the community which are under the community pillars. One of the activities carried out is managing finances including payment of monthly fees, bookkeeping, and financial audits. In its management, the treasurer still uses the manual method. So that the treasurer needs more time in recording and making monthly reports. Residents also often forget to pay dues so that they have dues dependents. So this study aims to design a neighborhood financial management application that is expected to help residents, treasurers, and chairmen at the River Village Housing Block E2 Malang City in managing financial activities. Human-centered design is used as a method in designing this user experience which begins with an analysis of the context and user needs which is then implemented in the form of a solution design. Then, a design evaluation was carried out using usability testing and a user experience questionnaire to 5 respondents which resulted in an effectiveness value of 82.8%, an efficiency value of 0.072 goals/second, with 85th score, grade A, adjective excellent, acceptable, promoter, and UEQ aspects with attractiveness 2.77, perspicuity 2.35, efficiency 2.85, dependability 2.9, stimulation 2.85, and novelty 2.5. In addition, design improvements and additional features were made according to the respondents' suggestions which resulted in an effectiveness value of 96.7% with an efficiency value of 0.088 goals/second. Thus, this research produces a prototype for further development.